Pointwise Estimates for the Coconvex Approximation of Differentiable Functions - Dzyubenko, H. A.; Zalizko, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We obtain pointwise estimates for the coconvex approximation of functions of the class W^r, r > 3.